Delayed neutron measurements of 232Th neutron-induced fission. (February 2015) - Ledoux, X.; Doré, D.; Mosconi, M.; Nolte, R.; Roettger, S.; Varet, S.
Highlights: The data between 4 and 10 MeV are totally new. The correlations between the measurements are calculated. The covariance matrix is calculated. Abstract: Delayed neutrons (DN) play an important role in nuclear reactor physics. Innovative critical reactor studies bring to light the need of new DN yields data. For the thorium fuel cycle DN data for 232 Th is needed. In the literature, significant discrepancies were observed for energies below 4 MeV and data are dispersed around 14 MeV. Therefore DN absolute yields from 232 Th fission have been determined at the PTB Ion Accelerator Facility in Braunschweig. A consistent set of data has been measured for incident neutrons with energies of 2, 3, 4, 6, 7, 10 and 16 MeV.